Geomorphic changes and socio-environmental impacts of recent sand mining in the Sakarya River, NW Turkey - Okur, Hilal; Erturac, Mehmet Korhan; Nicoll, Kathleen (Sage Publications Inc, 2024)
Analysis of multi-temporal satellite images from 1980 to 2019, complemented by geomorphic mapping and field study, indicate that loose sand extraction of Sakarya River deposits from the Adapazari Plain of NW Turkey significantly intensified during the last decade, and mining operations have caused complete and irreversible alteration of floodplain habitat in a total area amounting to similar to 970 hectares. Our reconstructions estimate the total amount of mined material over a 40-year period since 1980 as similar to 50 million m3, amounting to similar to 80 million tonnes of fluvial sand. These sand mine operations, like most around the world, are highly disruptive and destructive but remain unregulated, and neither extractions or environmental impacts are reported or monitored. Our independent study is first to directly assess sand extraction in altering the natural geomorphic setting of the Sakarya River and describe economic, environmental, and social impacts of mining operations. The high demand for loose sand used in cement and concrete infrastructure correlates with changes in Turkey's political economy, which increasingly focused on construction during the last quarter of the 20th century. Extractive sand mining in this region has caused substantial land loss, soil erosion and water table alterations, which have made agricultural land unsuitable for cultivation, and even destroyed most of the farmland supporting the villages, eliminating the traditional farming practiced for millennia. Continuous mining operations cause constant noise, heavy vehicle traffic and pollution. Furthermore, sand removal from the Sakarya river environment has significantly diminished sediment transport offshore to its delta in the Black Sea; the lower sediment yield diminishes coastal beach nourishment and is accelerating coastal land erosion regionally. The Sakarya case study we describe illustrates the need for (1) improved oversight of human agency that destroys riverine settings; and (2) regulations regarding long term environmental and social impacts of sand mining.
Keywords: Anthropocene; geomorphic changes; remote sensing; Sakarya River; sand mining; Turkey